2017
DOI: 10.1038/s41598-017-14588-2
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for transfer of plastic debris along a terrestrial food chain

Abstract: Although plastic pollution happens globally, the micro- (<5 mm) and macroplastic (5–150 mm) transfer of plastic to terrestrial species relevant to human consumption has not been examined. We provide first-time evidence for micro- and macroplastic transfer from soil to chickens in traditional Mayan home gardens in Southeast Mexico where waste mismanagement is common. We assessed micro- and macroplastic in soil, earthworm casts, chicken feces, crops and gizzards (used for human consumption). Microplastic concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
212
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 622 publications
(246 citation statements)
references
References 27 publications
3
212
0
5
Order By: Relevance
“…In addition to simply moving microplastics, biotic activities may also place them in pedological contexts they would rarely if ever otherwise occupy. Earthworms incorporate microplastics into their casts and burrow walls (Huerta Lwanga, Gertsen, et al, ; Huerta Lwanga et al, ; Huerta Lwanga, Mendoza Vega, et al, ; Prendergast‐Miller et al, ; Rillig, Ziersch, et al, ). These casts and burrows comprise a unique microhabitat that soil ecologists term the drilosphere (Andriuzzi, Bolger, & Schmidt, ; Sharma, Chandra, & Kanta, ).…”
Section: Faunal Effects: Dispersal and Positioningmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to simply moving microplastics, biotic activities may also place them in pedological contexts they would rarely if ever otherwise occupy. Earthworms incorporate microplastics into their casts and burrow walls (Huerta Lwanga, Gertsen, et al, ; Huerta Lwanga et al, ; Huerta Lwanga, Mendoza Vega, et al, ; Prendergast‐Miller et al, ; Rillig, Ziersch, et al, ). These casts and burrows comprise a unique microhabitat that soil ecologists term the drilosphere (Andriuzzi, Bolger, & Schmidt, ; Sharma, Chandra, & Kanta, ).…”
Section: Faunal Effects: Dispersal and Positioningmentioning
confidence: 99%
“…Though plastics obviously cannot actively hitchhike, they can still be passively dispersed on or inside soil organisms (Maaß et al, 2017;Rillig, Ziersch, et al, 2017;Zhu, Bi, et al, 2018). Although dispersal by springtails and mites has so far only been demonstrated in Petri dish arenas (Maaß et al, 2017;Zhu, Bi, et al, 2018), microplastics have been found in field-collected earthworm casts (Huerta Lwanga, Mendoza Vega, et al, 2017). Within soil pores, springtail movement may also facilitate influxes of small microplastic particles (Kim & An, 2019 In addition to simply moving microplastics, biotic activities may also place them in pedological contexts they would rarely if ever otherwise occupy.…”
Section: Faunal Effec Ts: D Is Per Sal and P Os Itioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Translocation of MP by earthworms (Huerta Lwanga et al, 2017a;Rillig et al, 2017b) and collembola (Maaß et al, 2017) could increase the exposure of other soil-dwelling species to MP. In addition, evidence on the accumulation of MP from soil to earthworms to chicken feces (Huerta Lwanga et al, 2017b) indicates that MP may enter terrestrial food webs through trophic transfers.…”
Section: Introductionmentioning
confidence: 99%